Erythema dyschromicum perstans (ashy dermatosis) during the treatment with infliximab in a child with Crohn disease - Sobjanek, Michał; Lange, Magdalena; Michajłowski, Igor; Lakomy, Joanna; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction . Erythema dyschromicum perstans (EDP) or ashy dermatosis is a rare, benign acquired disease characterized by macular hyperpigmentations. The cause of EDP is unclear although some drugs, toxic agents and internal disorders have been associated with this dermatosis. Objective . Presentation of the first case of the association between EDP and Crohn disease treated with infliximab. Case report . We present a case of a 15-year-old boy with Crohn disease who was treated with infliximab. During the treatment asymptomatic, hyperpigmented macules on the trunk were observed. Based on clinical and histopathological features the diagnosis of erythema dyschromicum perstans was established. Conclusions . Erythema dyschromicum perstans may be associated with Crohn disease and infliximab.